ATTEMPT TO UNDERSTAND PUBLIC-HEALTH RELEVANT SOCIAL DIMENSIONS OF COVID-19 OUTBREAK IN POLAND - JARYNOWSKI, ANDRZEJ; WÓJTA-KEMPA, MONIKA; PŁATEK, DANIEL; CZOPEK, KAROLINA (Society Register, 2020)
Recently, the whole of Europe, including Poland, have been significantly affected by COVID-19 and its social and economic consequences which are already causing dozens of billions of euros monthly losses in Poland alone. Social behaviour has a fundamental impact on the dynamics of the spread of infectious diseases such as SARS-CoV-2, challenging the existing health infrastructure and social organization. Modelling and understanding mechanisms of social behaviour (e.g. panic and social distancing) and its contextualization with regard to Poland can contribute to better response to the outbreak on a national and local level. In the presented study we aim to investigate the impact of the COVID-19 on society by: (i) measuring the relevant activity in internet news and social media; (ii) analysing attitudes and demographic patterns in Poland. In the end, we are going to implement computational social science and digital epidemiology research approach to provide urgently needed information on social dynamics during the outbreak. This study is an ad hoc reaction only, and our goal is to signal the main areas of possible research to be done in the future and cover issues with direct or indirect relation to public health.